Meetings with Costly Participation - Osborne, Martin J; Rosenthal, Jeffrey S; Turner, Matthew A (American Economic Review, 2000)
We study a collective decision-making process in which people interested in an issue may participate, at a cost, in a meeting, and the resulting decision is a compromise among the participants' preferences. We show that the equilibrium number of participants is small and their positions are extreme, and when the compromise is the median, the outcome is likely to be random. The model and its equilibria are consistent with evidence on the procedures and outcomes of U.S. regulatory hearings. (JEL D7, H0, L5)